Tindakan vandalisme di Perpustakaan Fakultas Ilmu Komunikasi Universitas Padjadjaran - Ilham Nur Muhammad; Neneng Komariah; Nuning Kurniasih (Universitas Padjadjaran, 2019)
The library is prone to vandalism towards library collections. The Faculty of Communication Sciences library as a university library often experiences vandalism, ranging from labeling, tearing up, page folding, delay in returning books, and loss of books. This study aimed to determine the cognitive aspects of the sub-variables of knowledge and understanding of users on the act of vandalism in the Library of the Faculty of Communication Sciences, Padjadjaran University. The research method used descriptive survey method through a quantitative approach. This study included 121 respondents consisting of students of Faculty of Communication Sciences, class of 2015 who were selected using simple random sampling technique with distribution of respondent composition: Public Relations 10 respondents, Communication Sciences 47 respondents, Information and Library Science 22 respondents, Journalism 16 respondents, Communication Management 18 respondents, and TV and Film 8 respondents. Study results showed that the cognitive aspects of the users in the act of vandalism were in the category of high and favorable, the users had knowledge and understanding which supported according to the statement about the attitude proposed against acts of vandalism. Based on knowledge indicators, data obtained showed respondents did not agree with vandalism act, while based on the indicators of understanding, data obtained showed respondents agree that vandalism could harm the library users. Overall, the attitude of users is in the favorable category meaning that library users support disagreement on vandalism in the Library of the Faculty of Communication Sciences, Padjadjaran University.